The role of interleukin-1ß and interleukin-33 in atopic dermatitis - Rania M. Abdel Hay; Noha F. Ibrahim; Dina Metwally; Laila A. Rashed (Our Dermatology Online, 2013)
Introduction: Interleukin-1 super family is a group of cytokines that play a role in the regulation of immune and inflammatory responses. Interleukin-33 is a member of this family and is known to induce expression of the T helper2 cytokines that are important players in atopic dermatitis. Aim: To evaluate the expression of interleukins-1ß and 33 as T helper2 cytokines inducers in patients with atopic dermatitis. Materials andMethods: This study included 20 atopic patients and 20 apparently healthy individuals serving as controls. Skin biopsies from all participants will be examined for detection of interleukins-1ß and 33 by ELISA technique.Results: Both interleukins were statistically higher (P<0.001) in patients than in controls. A statistically significant (P=0.011) highest levels of interleukin-33 was detected in severe cases of atopics when compared to mild and moderate cases. A significant correlation (r=0.632, P=0.003) between both interleukins was detected in atopics.Conclusions: This is the first study to evaluate both interleukin-1ß and33 together in atopic patients. Both interleukins could play a role in the recruitment of lymphocytes during the inflammatory reaction in atopic dermatitis and could be targeted in the treatment of resistant cases.